PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, BUDAYA ORGANISASI, DAN KOMUNIKASI TERHADAP PEGAWAI APARATUR SIPIL NEGARA KOTA BEKASI - Ananda, Prajitha Dwi; Ruswidiono, Wasisto (E-Jurnal Manajemen Trisakti School of Management (TSM), 2022)
The purpose of this study was to examine the effect of independent variables (X) which are transformational leadership, organization culture, and communication on the dependent variable (Y) work discipline State Civil Apparaturs Dinas XYZ Bekasi City. The method used in this study is causality. This study uses purposive samples. Respondents involved in this study were 77 employees. Data collection is done by distributing questionnaires. And the method for data analysis in this research is multiple linear regression processed. Based on the hypothesis test the results of this study flexibility of transformational leadership, and communication affect the work discipline State Civil Apparaturs. While the organization culture does not affect work discipline.